2006
DOI: 10.1016/j.bbamem.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A Fourier transform infrared microspectroscopic imaging investigation into an animal model exhibiting glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is a highly malignant human brain tumour for which no cure is available at present. Numerous clinical studies as well as animal experiments are under way with the goal being to understand tumour biology and develop potential therapeutic approaches. C6 cell glioma in the adult rat is a frequently used and well accepted animal model for the malignant human glial tumour. By combining standard analytical methods such as histology and immunohistochemistry with Fourier Transform Infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…It should be noted that various multivariate approaches have been employed for sensitive and selective classification of the grade and origin of brain tumours, i.e. uhCA [120,122], K-means [118,121,123], SImCA (Soft Independent modeling of Class Analogy) [119,123], PCA [123,125], LdA [116][117][118]124] and their combinations. In this section, we introduce the reader to the results of FtIR imaging of the brain tissue in neurodegenerative disorders such as Alzheimer's and Parkinson diseases, multiple sclerosis and others, for which the etiology or clinical diagnosis have not been clearly revealed, and are still the subject of intensive investigations.…”
Section: Brain Tissuementioning
confidence: 99%
“…It should be noted that various multivariate approaches have been employed for sensitive and selective classification of the grade and origin of brain tumours, i.e. uhCA [120,122], K-means [118,121,123], SImCA (Soft Independent modeling of Class Analogy) [119,123], PCA [123,125], LdA [116][117][118]124] and their combinations. In this section, we introduce the reader to the results of FtIR imaging of the brain tissue in neurodegenerative disorders such as Alzheimer's and Parkinson diseases, multiple sclerosis and others, for which the etiology or clinical diagnosis have not been clearly revealed, and are still the subject of intensive investigations.…”
Section: Brain Tissuementioning
confidence: 99%
“…Tissue samples from these animal models were studied by IR spectroscopy [35,64] and Raman spectroscopy [26,36]. Raman images were collected from brain-tissue blocks using a fiberoptic probe and a motorized stage [26].…”
Section: Brain Tumors and Neurodegenerative Diseasesmentioning
confidence: 99%
“…This suggests that chemical trace elements may also contribute to neurobiology of gliomas. In turn, previous studies have shown that FTIR spectroscopy, coupled with various sophisticated statistical techniques, could be a powerful tool to trace macromolecular processes underlying vascularization, angiogenesis, necrosis and apoptosis in human and animal models of brain gliomas infiltration [11] . A number of researchers have reported that these processes are associated with pronounced modifications in protein secondary structure.…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies show high potential of FTIR spectroscopy to develop into a powerful tool in the diagnosis of cancer. Nonetheless, there is still a need to utilize more sophisticated techniques for both the data analysis and processing to extract more details from FTIR spectra [11] . This may potentially assist modern pathology by taking into account more molecular factors, sometimes tremendously subtle, to improve our understanding of biochemical processes underlying a great variety of diseases as well as for further FTIRbased classification issues [11] .…”
Section: Introductionmentioning
confidence: 99%